PEMBUATAN KONTEN PEMBELAJARAN YANG MENARIK BERBASIS PEMECAHAN MASALAH DI SMP BP-ALMUNAWAROH - Dian Mayasari; Sadrack Luden Pagiling (Jubaedah : Jurnal Pengabdian dan Edukasi Sekolah (Indonesian Journal of Community Services and School Education), 2021)
Creating engaging content is the foundation for teachers to improve the quality of their students' learning. The training is designed to assist teachers in creating engaging learning experiences for their students and increasing student motivation to learn. Because of the current COVID-19 pandemic, all levels of education require distance learning. As a result, all teachers must deliver lessons to students remotely. Furthermore, this training is intended to prepare teachers to adapt to technological advancements because learning and teaching activities may be carried out online or offline in the future.